Проблеми морфології суцвіття видів роду Amaranthus L.: типологія, структура цимоїдів, метатопії - Andrushchenko, O.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
For species of the genus Amaranthus L. there is no uniform name of type of compound inflorescence. It is proposed to use definition "thyrs". The features of cymose inflorescences are considered. For the first time concaulescentia in inflorescences of species Amaranthus paniculatus L. and A. hybridus L. was described.